2015
DOI: 10.1007/s00259-015-3131-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrated PET/MRI for whole-body staging of patients with primary cervical cancer: preliminary results

Abstract: The present study demonstrates the high potential of integrated PET/MRI for the assessment of primary tumor and the detection of lymph node metastases in patients with cervical cancer. Providing additional prognostic information, PET/MRI may serve as a valuable diagnostic tool for cervical cancer patients in a pretreatment setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 32 publications
3
78
2
3
Order By: Relevance
“…However, several dedicated imaging centres, report high TVUS accuracy for cervical cancer staging and assessment of parametrial involvement, comparable to those of MRI [22,23] . Hybrid imaging (PET-CT or PET-MRI) is superior to conventional cross-sectional techniques for identifying metastatic lymph nodes, with excellent diagnostic accuracy, ranging from 85%-99% [24,25] . However, its role in the initial evaluation of cervical cancer has not been established.…”
Section: Parametrial Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several dedicated imaging centres, report high TVUS accuracy for cervical cancer staging and assessment of parametrial involvement, comparable to those of MRI [22,23] . Hybrid imaging (PET-CT or PET-MRI) is superior to conventional cross-sectional techniques for identifying metastatic lymph nodes, with excellent diagnostic accuracy, ranging from 85%-99% [24,25] . However, its role in the initial evaluation of cervical cancer has not been established.…”
Section: Parametrial Involvementmentioning
confidence: 99%
“…Accuracy of PET-CT for local staging of cervical cancer is moderate (53.3%). PET-MRI may be promising for the assessment of primary tumor, with sensitivity and specificity values over 90%, but further studies with larger patient populations are needed to support clinical implementation [25] . MRI is the preferred imaging modality for evaluating local extent of cervical cancer due to its high contrast resolution which enables differentiation between cancerous and normal tissues [5,26,27] .…”
Section: Parametrial Involvementmentioning
confidence: 99%
“…Therefore, an accurate staging and detection of LNs metastases is essential to ensure appropriate treatment planning and prediction of prognosis for cervical cancer patients [5] .…”
mentioning
confidence: 99%
“…General expectations for PET/MRI are high. A recent study assessed the efficacy of integrated PET/MRI for the whole body staging of patients with primary CC (31). In their preliminary results, the authors concluded that integrated PET/MRI had a high potential to accurately assess primary tumors and detect LNM in patients with CC.…”
Section: Discussionmentioning
confidence: 99%